Petroleum System Modeling of Halfaya Oil Field South of Iraq - W. Al- Marsomy, Shahad; K. Al- Ameri, Thamer (Iraqi Journal of Science, 2023)
The petroleum system of Halfaya oil field shows that the hydrocarbon generation of these Formations such as Sha′uiba and Nahr Umr are immature and have generated few oil TR ≤ 50% which are neglected as compared to Formations below them which are very rich source rock. The Formations of Yamama, Ratawi and Sulaiy are mature with TR ≤ 100%. Other Formations such as Sargelu ,Najma,Zubair and Gotnia are with very high maturity with TR ≥ 100% and completely generated hydrocarbon and depleted after hydrocarbon are expelled and migrate to reservoir rock of structure traps and this study indicates that the major seals of Upper Jurassic are Gotnia and Allan Formations and of Middle Miocene is LowerFars fatha Formation.